Phosphorous Acid Promoted Hydration–Condensation of Aromatic Alkynes with Aldehydes Affording Chalcones in an Oil/Water Two-Phase System - Zhou, Yongbo; Li, Zhongwen; Yang, Xiao; Chen, Xiulin; Li, Mei; Chen, Tieqiao; Yin, Shuang-Feng (Synthesis, 2016)
A simple and environmentally benign method was developed for the synthesis of chalcones in high to excellent yields by a phosphorous acid promoted alkyne–aldehyde hydration–condensation in an oil/water two-phase system. The method is the first efficient protocol for the preparation of chalcones that is mediated by a simple Brønsted acid in a two-phase system.
Keywords: phosphorous acids; two-phase systems; chalcones; hydration; condensation; green chemistry